Parental involvement in children's education: Case studi in SDN 1 Wates, Slahung, Ponorogo - Heri Setiawan; A. Hari Witono; Styo Mahendra Wasito Aji; Asri Fauzi; Heri Hadi Saputra (Priviet Social Sciences Journal, 2025)
This study focuses on describing the forms of parental involvement in children's education at SDN 1 Wates, Slahung District, Ponorogo Regency. This study focuses on describing the forms of parental involvement in student learning activities, involvement in extracurricular activities, and various obstacles that accompany parental involvement. This study was conducted using a case study design. The selected research subjects were one principal, six class teachers, and four parents, consisting of two parents of lower grade students and two guardians of upper grade students. Data collection techniques were carried out through observations, in-depth interviews, and document analysis. The instruments used were observation, interview, and document analysis guidelines. The data analysis techniques used were data reduction models, data displays, and conclusive drawing/verification. Data validation was carried out by triangulation, namely, source triangulation. In general, parental involvement at SDN 1 Wates consists of two forms: involvement in children's education at home and involvement in children's education at school. In supporting children's education at home, parents do the following: (1) accompany and motivate children while studying; (2) communicate regarding the development of children's learning and fluency; (3) provide learning facilities; (4) communicate with teachers; (5) become volunteers; and (6) attend meetings at school. In addition to participating in children's education, parents are involved in extracurricular activities, such as scouts, TPA, gamelan, and traditional dance. Various factors that inhibit the implementation of partnerships and the involvement of students' parents based on the statements of the principal, teachers, and parents of students at SDN 1 Wates are: (1) economic factors and parents' busyness; (2) communication obstacles; (3) parents' educational background; and (4) parents' self-efficacy regarding their capacity to be involved in their children's education